1997
DOI: 10.1183/09031936.97.10092139
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelium as an effector of inflammation: molecular regulation of secondary mediators

Abstract: Deleterious environmental stimuli cause the airway epithelium to respond with increased secretions of mucus, reaction of oxygen/nitrogen species, changes in ciliary beating, and the influx of inflammatory cells. The epithelium is a target for factors released by infiltrating inflammatory cells, and has recently been shown to serve as an effector of such inflammation. Molecular mechanisms regulating production of secondary inflammatory mediators (cytokines, lipid mediators, and reactive oxygen/nitrogen species)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 87 publications
2
101
0
1
Order By: Relevance
“…IL-6 has been shown to be involved in bleomycin-induced inflammation 28,29 and is produced by a variety of cell types, including epithelial cells and macrophages. 30,31 There is also good evidence that secretion of IL-6 is regulated through NF B 32 and NF B consensus binding sites have been identified in the promoter of the IL6 gene. 33,34 We also measured the effect of NF B decoy ODN on total and differential cell counts, as it is well documented that inflammatory cell chemokines, such as macrophage inflammatory protein-1␣ and macrophage inflammatory protein-2, which are involved in the generation of bleomycin-induced lung damage, 28,35 are regulated through NF B.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has been shown to be involved in bleomycin-induced inflammation 28,29 and is produced by a variety of cell types, including epithelial cells and macrophages. 30,31 There is also good evidence that secretion of IL-6 is regulated through NF B 32 and NF B consensus binding sites have been identified in the promoter of the IL6 gene. 33,34 We also measured the effect of NF B decoy ODN on total and differential cell counts, as it is well documented that inflammatory cell chemokines, such as macrophage inflammatory protein-1␣ and macrophage inflammatory protein-2, which are involved in the generation of bleomycin-induced lung damage, 28,35 are regulated through NF B.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that airway epithelia play an active role in the development of chronic airway inflammatory diseases [1-3, 7, 39]. For example, the airway epithelia secrete a variety of cytokines to initiate immune responses [1,3], and contribute to the irreversible structural changes of the airway that are referred to as 'airway remodeling', which occurs in patients with asthma [3,7]. Our findings that both ESE-1 and ESE-3 are highly inducible in bronchial epithelial cells suggest that these transcription factors may be critical in the regulation of airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a pleiotropic cytokine with a variety of biological activities not only in immune regulation, hematopoiesis and oncogenesis, but also in inflammation [44]. Moreover, IL-6 is considered a key modulator in chronic airway inflammatory disease such as asthma [1,45,46]. Airway epithelial cells can synthesize and release IL-6 in response to inflammatory stimuli.…”
Section: Ese-3mentioning
confidence: 99%
See 2 more Smart Citations